How do immigrants spend their time? The process of assimilation - Daniel S. Hamermesh; Stephen J. Trejo (Institute for the Study of Labor (IZA), 2010)
Using 2004-2008 data from the American Time Use Survey, we show that sharp differences between the time use of immigrants and natives become noticeable when activities are distinguished by incidence and intensity. We develop a theory of the process of assimilation - what immigrants do with their time - based on the notion that assimilating activities entail fixed costs. The theory predicts that immigrants will be less likely than natives to undertake such activities, but conditional on undertaking them, immigrants will spend more time on them than natives. We identify several activities - purchasing, education and market work - requiring the most interaction with the native world, and these activities more than others fit the theoretical predictions. Additional tests suggest that the costs of assimilating derive from the costs of learning English and from some immigrants' unfamiliarity with a high-income market economy. A replication using the 1992 Australian Time Use Survey yields remarkably similar results.
Keywords: J11; J22; 330; Time use; fixed costs; incidence; intensity; Migranten; Zeitbudgetforschung; Soziale Integration; Schätzung; USA; Vergleich; Australien